PELATIHAN KOMUNIKASI DASAR BERBASIS AKTIVITAS WISATA BAGI PEMELAJAR BIPA DASAR: PENGABDIAN KEPADA MASYARAKAT BAGI MAHASISWA KOREA SELATAN DI BALI - Made Rina; Putu Dian Yuliani Paramita (Sewagati, 2025)
This community service program aims to improve the basic Indonesian communication skills of a BIPA learner from South Korea, Jeung Min Yeoung, who has been residing in Bali for nine months. The training was designed using a tourism-based learning approach that integrates language practice into situational contexts, such as visits to local destinations, interactions with the community, and simulations of everyday conversations. This approach provides the learner with more natural language exposure and experiences relevant to daily life in Bali. The program included an initial language assessment, the development of communicative materials, intensive mentoring, and a progress evaluation. The results of the activity indicate an increase in the learner’s confidence and fluency in using basic expressions for asking questions, introducing oneself, shopping, and engaging in social interactions. This program is expected to serve as a model for tourism-based BIPA learning to support the development of communicative competence among foreign learners.